Ціннісні домінанти в епістолярії Бориса Грінченка - Марчук, Л.М. (Лексикографічний бюлетень, 2014)
The peculiarity of epistolary Borys Hrinchenko’s heritage is defined in lett er genre forms diversity, in deepness of philosophic quests, in inexhaustibility and sincerity of feelings, in linguistic and stylistic experiments and in careful att itude to epistolary canons. Literary perfection of individual language, aesthetic taste are found in selection of lexical means of thoughts expression. Th e vocabulary of lett er’s language contains a great number of value lexical units, which are used as the stylistic att ribute of individual style. Th e key image-symbol in Borys Hrinchenko’s correspondence became Ukraine. Th e Borys Hrinchenko’s correspondence — is the striking example of the fact, how obsessed must be the person, who made his contribution in independence of a new state Ukraine.